Recount board game on students’ speaking skills - Rohmaniyah; Devi Enggar Nastiti; Choiril Anwar (Penerbit STKIP PGRI Bangkalan, 2019)
This study was aimed at finding the effectiveness of “Recount Board Game” in teaching and learning students’ speaking skills to the the tenth grade students of SMA Islam Sultan Agung 3 Semarang, Indonesia. The researchers used quasi experimental method and chose two classes for it, they were: X-1 as experimental class with 33 students and X-2 as control class with 34 students. In the both of classes, researchers conducted the research in three steps: pre-test, treatment, and post-test to look for the data then were analyzed by using SPSS for Windows Version 21.0. The result of this study showed that there was a significant difference in the result of pre-test and post-test in both of two classes. The mean of pre-test in experimental group was 59.19 and the mean of post-test in experimental group was 83.03. Whereas the mean of pre test in control group was 57.65 and the mean of the post-test in control group was 76.47. Based on independent t-test, t-value was higher than t-table (4.474 ˃ 1.997) and p < 0.05 (0.000< 0.05). It meant that there was a significant difference in the student’s skills achievement between the experimental and control groups. So, it could be concluded that H1 was accepted and the use recount board game was effective in teaching students’ speaking skills.